Ethical issues in nursing - Hunt, Geoffrey (Professional ethics, 1994)
This book takes nursing ethics beyond the stock `moral concepts' to a critical examination of the fundamental assumptions underlying the very nature of nursing. It deals openly with controversial issues faced by nurses, such as euthanasia and HIV